Mitochondrial regulation in skeletal muscle: A role for non‐coding RNAs?. Issue 8 (31st July 2018) - Silver, Jessica; Wadley, Glenn; Lamon, Séverine
Abstract : New Findings: What is the topic of this review ? This article draws evidence from the current literature to support the hypothesis that non‐coding RNA‐mediated gene regulation takes place in the mitochondria. An emphasis is put on skeletal muscle. What advances does it highlight ? This review highlights the potential role of microRNAs and long non‐coding RNAs in mitochondrial gene regulation. The discovery of a new level of skeletal muscle mitochondria‐controlled gene regulation presents exciting perspectives for our understanding of skeletal muscle physiology in health and disease. Abstract: Skeletal muscle is a highly metabolic tissue characterized by high mitochondrial abundance. As such, skeletal muscle homeostasis relies on the tight control of mitochondrial gene expression to ensure efficient mitochondrial function. Mitochondria retain a conserved genome from prokaryotic ancestors, and mitochondrial gene regulation relies on communication between mitochondrial‐ and nuclear‐encoded transcripts. Small and long non‐coding RNAs (ncRNAs) have regulatory roles in the modulation of gene expression. Emerging evidence demonstrates that regulatory ncRNAs, particularly microRNAs (miRNAs) and long ncRNAs (lncRNAs), localize within the mitochondria in diverse physiological and pathological states. These molecules present intriguing possibilities for the regulation of mitochondrial gene expression. Current research suggests that all known miRNAs are encoded by the nuclear genome but can target mitochondrial genes. Initial investigations demonstrate direct interactions between the muscle‐enriched miR‐1 and miR‐181c and mitochondrial transcripts, suggesting advanced roles of miRNAs in mitochondrial gene regulation. This review draws evidence from the current literature to discuss the hypothesis that a level of ncRNA‐mediated gene regulation, in particular miRNA‐mediated gene regulation, takes place in the mitochondria. Although ncRNA‐mediated regulation of the mitochondrial genome is a relatively unexplored field, it presents exciting possibilities to further our understanding of mitochondrial metabolism and human muscle physiology. Abstract :